Interactive regulation of affect in postpartum depressed mothers and their infants: an overview - Reck, Corinna; Hunt, Aoife; Fuchs, Thomas; Weiss, Robert; Noon, Andrea; Möhler, Eva; Downing, George; Tronick, Edward Z.; Mundt, Christoph (Psychopathology, 2004)
Specific patterns of interaction emerging in the first months of life are related to processes regulating mutual affects in the mother-child dyad. Particularly important for the dyad are the matching and interactive repair processes. The interaction between postpartum depressed mothers and their children is characterized by a lack of responsiveness, by passivity or intrusiveness, withdrawal and avoidance, as well as a low level of positive expression of affect. Thus, an impaired capability to regulate the child’s affect has been demonstrated in depressed mothers. Maternal aggression, neglect toward infants, infanticidal thoughts, as well as infanticidal behavior are mainly linked to severe postpartum depression, especially with psychotic symptoms. The findings on mother-child interaction reported in this paper are based on mothers with mild to moderate depressive disorders without psychotic symptoms. Considering the stability of interaction patterns in the course of depressive illness as well as the long-term consequences of these interactions, it seems surprising that there are still few systematic studies of depressed mothers interacting with their infants.In connection with an overview on these issues, treatment models forparent-infant psychotherapy are discussed.